Peran Guru dalam Membentuk Karakter Anak Usia Dini di TK Negeri Pembina Kecamatan Kota Timur Gorontalo - Wulandari Dasi; Nia Purnamasari; Hizra Qoristiva; Risjianti Maida; Nursifa Y. Hulopi; Meilan Baba (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
Teachers play a pivotal role in shaping the character of early childhood through directed and loving education. At this critical developmental stage, foundational values such as honesty, responsibility, empathy, and discipline begin to form. Teachers serve not only as educators but also as role models who exemplify positive behavior. Through daily interactions, teachers help children understand social norms, manage emotions, and build healthy relationships with peers and the environment. Character education is often delivered through play, storytelling, or engaging group discussions, making moral values accessible and understandable for children. Teachers also create a supportive learning environment where children feel safe to explore, learn, and interact, fostering self-confidence and resilience.